Taxonomic revision of doubtful Brazilian freshwater shrimp species of genus Macrobrachium (Decapoda, Palaemonidae) Revisão taxonômica das espécies brasileiras duvidosas de camarões de água doce do gênero Macrobrachium (Decapoda, Palaemonidae) - Leonardo G. Pileggi; Fernando L. Mantelatto (Iheringia: Série Zoologia, 2012)
The freshwater prawns of the genus Macrobrachium Spence Bate, 1868 are widely distributed in rivers of tropical and subtropical regions and represent an interesting group with controversial taxonomy. The morphological characters traditionally used to separate species have shown a high intraspecific variation. Doubts about the status of M. birai Lobão, Melo & Fernandes, 1986, M. holthuisi Genofre & Lobão, 1978 and M. petronioi Melo, Lobão & Fernandes, 1986 have been arisen due to the high resemblance of the former two species with M. olfersi (Wiegmann, 1836), and the latter one with M. potiuna (Müller, 1880). Therefore, we performed a detailed morphological analysis of these species, including new characters not usually used in the species recognition. The present results here with molecular data lead us to conclude that M. birai and M. holthuisi are junior synonyms of M. olfersi, and M. petronioi is a junior synonym of M. potiuna. Considering these synonymies, 17 valid species are now reported for the Brazilian territory. Os camarões de água doce do gênero Macrobrachium Spence Bate, 1868 encontram-se amplamente distribuídos em rios de regiões tropicais e subtropicais e representam um grupo com taxonomia controversa. Os caracteres morfológicos comumente utilizados para separação de espécies apresentam uma grande variação intraespecífica. Dúvidas sobre o status taxonômico de M. birai Lobão, Melo & Fernandes, 1986, M. holthuisi Genofre & Lobão, 1978 e M. petronioi Melo, Lobão & Fernandes, 1986 foram levantadas devido à alta similaridade morfológica das primeiras com relação à M. olfersi (Wiegmann, 1836) e da última com relação à M. potiuna (Müller, 1880). Assim, foi realizada uma análise morfológica detalhada de tais espécies, incluindo novos caracteres comumente não utilizados na identificação dos táxons. A partir dos resultados obtidos, juntamente com dados moleculares, concluímos que M. birai e M. holthuisi são sinônimos-júnior de M. olfersi, e M. petronioi é sinônimo-júnior de M. potiuna. Portanto, considerando-se tais sinonímias, são reportadas 17 espécies válidas para o território brasileiro.